Hyperuricemia in Destabilization of Endothelial Function in Adolescents with Arterial Hypertension - N.M. Korenev; I.N. Bessonova; T.S. Vvedenskaya (Zaslavsky O.Yu., 2013)
The objective of this work was to study the correlation of uric acid level in blood serum and parameters of endothelial function and non-specific inflammation in adolescents with arterial hypertension considering their body weight. In the most of patients with arterial hypertension endothelial dysfunction was detected; endothelium-dependent vasodilation was more altered in the patients with obesity and especially in those with hyperuricemia. An increase in C-reactive protein serum level was mainly associated with obesity; a decrease in systolic-diastolic ratio - with hyperuricemia.